THE CONCEPT OF TRUTH IN LANGUAGE USE: WITTGENSTEIN'S THOUGHTS AND IMPLICATIONS FOR ENGLISH LANGUAGE TEACHING - Nurul, Ade; Ayultri; Nurhayati, St (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the concept of truth in language use according to Ludwig Wittgenstein’s philosophical thought and its implications for English language teaching in EFL (English as a Foreign Language) classrooms. The research employs a qualitative approach using library research methods through the analysis of Wittgenstein’s works and recent academic literature in the fields of philosophy of language and pedagogy. Data were obtained from secondary sources, including relevant books and peer-reviewed journal articles, and analyzed using content analysis techniques. The findings indicate that Wittgenstein’s concept of “truth as use” directly influences a more communicative and contextual approach to English language teaching. The main finding reveals that a language-games-based approach enhances students’ communicative performance by balancing grammatical accuracy and social acceptability. Moreover, the results emphasize that learning evaluation should not only focus on propositional truth but also on functional truth, reflecting learners’ ability to use language appropriately in social contexts. Consequently, this research contributes theoretically by bridging Wittgenstein’s philosophy of language with modern pedagogical practices and offers a conceptual foundation for developing more pragmatic curricula and evaluation strategies in English language teaching.